The impact of senescence-associated T cells on immunosenescence and age-related disorders - Yuji Fukushima; Nagahiro Minato; Masakazu Hattori (BMC, 2018)
Abstract Immunosenescence is age-associated changes in the immunological functions, including diminished acquired immunity against infection, pro-inflammatory traits, and increased risk of autoimmunity. The proportions of memory-phenotype T cells in the peripheral T cell population steadily increase with age, but the relationship between this change and immunosenescent phenotypes remains elusive. Recently, we identified a minor memory-phenotype CD4+ T cell subpopulation that constitutively expressed PD-1 and CD153 as a bona fide age-dependent T cell population; we termed these cells senescence-associated T (SA-T) cells. SA-T cells exhibit characteristic features of cellular senescence, with defective T cell receptor-mediated proliferation and T cell cytokine production. However, upon T cell receptor stimulation, SA-T cells secrete abundant atypical pro-inflammatory cytokines such as osteopontin and chemokines, reminiscent of the SA-secretory phenotype. In addition to aging, SA-T cells accumulate and cause persistent inflammation in tissues following a wide range of insults including immune complex deposition, metabolic stresses, vascular damages, and tumors. In this review, we summarize the recent understanding of immunosenescence with particular focus on SA-T cells and their role in various age-related disorders.